Energia solar disponível e energia gerada em sistemas fotovoltaicos em diferentes inclinações e orientações de telhados de edificações - Vargas, Michael Collin (2021)
The present work aimed to determine the solar energy available at different inclinations and orientations of building roofs in the four seasons of the year, using data of global solar irradiation in the horizontal plane, temperatures and wind speed. The inclined hourly solar irradiation and the energy generated by photovoltaic systems of different capacities installed in Cascavel -PR, with different orientations and inclinations and roof types (ceramic, fiber cement and metal) were simulated. The daily horizontal global solar irradiation and wind speed data from SWERA (Solar and Wind Energy Resource Assessment) were used to simulate the daily inclined global solar irradiation in the PVSyst software. Thus, also with the help of the software, the energy generated by photovoltaic systems of different capacities installed in Cascavel - PR, with different orientations and roof inclinations was determined. Consequently, the levels of losses in different seasons of the year were calculated and an analysis of the economic viability of the enterprises was made. Thus, the losses, profits and yield of the systems were compared. Solar panels installed on ceramic roofs oriented towards the North provide better energy production yield throughout the year in comparison with metal and fiber cement roofs. However, for the other orientations (South, East, and West), the losses for ceramic roofs were twice as high as for metal and fiber-cement roofs relative to their respective North-oriented slopes. With respect to orientation, north-oriented roofs receive more irradiation annually, and therefore produce more energy. This is followed by East, West and South as the most unfavorable condition.